Change in Functional Beta Cell Capacity With Time Following Autologous Islet Transplantation. Issue 5 (May 2019) - Ali, Khawla F.; San Martin, Vicente T.; Walsh, R. Matthew; Bottino, Rita; Stevens, Tyler; Trucco, Massimo; Hatipoglu, Betul
Abstract : Objectives: Autologous islet transplantation (AIT) is performed to preserve insulin secretory function in chronic pancreatitis patients undergoing total pancreatectomy (TP). No data exist on the effect of time lapse on beta cell function post TP-AIT. We aimed to investigate the factor of time lapse on beta cell function following TP-AIT. Methods: Retrospectively, we identified 31 adult patients with chronic pancreatitis who underwent TP-AIT between 2008 and 2016. Changes in beta cell function were assessed using (1) BETA-2 scores and (2) analysis of posttransplant mixed-meal tolerance testing. Results: Significant decrease in functional beta cell capacity expressed by BETA-2 scores was seen in the first 2 years following TP-AIT, with an annual decrease of 6.3 points in median BETA-2 score (interquartile range, 4.6–11.6; P = 0.002). In the mixed-meal tolerance testing analysis, nonsignificant trends toward higher glucose, lower insulin, and lower C-peptide were seen with time lapse. Additionally, higher hemoglobin A1c values ( P = 0.033) and higher insulin requirements ( P = 0.04) were seen with longer follow-up after AIT. Conclusions: A steady drop in functional beta cell capacity was observed in the 2 years following TP and AIT. To our knowledge, to date this is the first report of the BETA-2 score applicability in the AIT setting.